'The best guess for the future?' Teachers' adaptation to open and flexible learning environments in Finland. Issue 3 (3rd July 2021) - Niemi, Kreeta
ABSTRACT: Finnish education has recently experienced reforms with respect to guidelines forming the curriculum framework for basic education and school architecture. Since 2016, all new schools incorporate open and flexible design, at least to some extent. The more open school design challenges the conventional organisation of space and pre-defined structures and interaction practices. This study investigates how teachers both adapt and are affected by new demands for pedagogy, team teaching and teacher-student relationships. Interview data of 21 teachers of six modern schools are reviewed through thematic analysis. The new school layouts provided some incongruence with the teachers' aims and their preferred practices. Although many teachers were dissatisfied with the new or remodelled space solution, they felt that their school had developed as a learning community, with improved collegiality, and good experiences of team teaching had increased. Shared vision, open discussion, commitment and enough time for preparation had helped in adaptation. Lacking arguments behind school transformation and the dismissal of ideas of school design hindered adaptation. This study suggests that teachers should have a greater voice in the school design process, and the needs of learners should be carefully considered, ensuring optimal physical and pedagogical context for effective and collaborative learning.